Perancangan Sistem Manajemen Akuntansi Koperasi Berbasis Website pada KPRI Bina Cipta - R Widya Henisaputri (Journal of Digital Ecosystem for Natural Sustainability, 2026)
Cooperatives require integrated information systems to improve operational efficiency, financial transparency, and service quality in response to ongoing digital transformation. However, many cooperative accounting systems are still developed without a systematic requirements engineering approach, resulting in fragmented business processes and limited integration among organizational services. This study aims to design a web-based cooperative accounting management system for KPRI Bina Cipta by applying the Viewpoint-Oriented Requirements Definition (VORD) approach to systematically identify stakeholder requirements. A case study methodology was employed through interviews, direct observations, and literature review. System requirements were analyzed using VORD, followed by system modeling with Unified Modeling Language (UML) and implementation using PHP, CodeIgniter, and MySQL. Functional verification was conducted through black-box and white-box testing. The proposed system integrates member administration, savings and loan management, merchandise transactions, payment confirmation, and financial reporting within a single web-based platform. The VORD approach enabled the identification of stakeholder-specific requirements, resulting in a more structured system design, improved data integration, enhanced transaction traceability, and greater accessibility of financial information for cooperative members. This study contributes to the implementation of requirements engineering in cooperative information system development and provides a digital solution that supports sustainable digital transformation and governance within community-based financial organizations.